2007
DOI: 10.1039/b701380a
|View full text |Cite
|
Sign up to set email alerts
|

Novel conducting nanocomposites: synthesis of triphenylene-covered gold nanoparticles and their insertion into a columnar matrix

Abstract: Gold nanoparticles fully covered with triphenylene-based discotic liquid crystals (DLCs) were synthesized and dispersed in a columnar matrix. The thermophysical properties of these nanocomposites, studied using polarizing optical microscopy, differential scanning calorimetry and small angle X-ray diffraction studies (SAXS), confirm their insertion into the columnar matrix. The presence of the gold nanoparticles in the triphenylene-based DLCs does not disturb the nature of the mesophase other than altering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 33 publications
3
63
0
Order By: Relevance
“…Randomly distributed GNPs ( Figure 6) can form charge transfer complexes when sandwiched between discotic cores, thus enhancing the conductivity of the system. 44 Similar behavior has been observed when triphenylene-based discotics were doped with the electron-deficient trinitrofluorenone molecule. 24 Holt et al 45 observed a similar enhancement (10 6 ) in electrical conductivity in the hexagonal columnar phase of a triphenylene-based DLC upon doping with 1% methylbenzene thiol-covered GNPs.…”
Section: Gnps In Discotic Lcssupporting
confidence: 56%
See 2 more Smart Citations
“…Randomly distributed GNPs ( Figure 6) can form charge transfer complexes when sandwiched between discotic cores, thus enhancing the conductivity of the system. 44 Similar behavior has been observed when triphenylene-based discotics were doped with the electron-deficient trinitrofluorenone molecule. 24 Holt et al 45 observed a similar enhancement (10 6 ) in electrical conductivity in the hexagonal columnar phase of a triphenylene-based DLC upon doping with 1% methylbenzene thiol-covered GNPs.…”
Section: Gnps In Discotic Lcssupporting
confidence: 56%
“…44 Thus, the reduction of gold salt in the presence of thiol-functionalized triphenylene derivative yields discotic-decorated GNPs (Figure 4). In the virgin state, these discoticdecorated GNPs were found to be non-mesomorphic, but they could Remarkably, DC electrical conductivity measurements under ambient conditions show an enhancement of conductivity by six orders of magnitude ( Figure 5) upon doping just 1% of GNPs into DLCs.…”
Section: Gnps In Discotic Lcsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In another innovative approach, we realized that the conductivity of DLCs can be enhanced by several orders of magnitude by dispersing a very small amount of metallic, semiconducting or carbon nanoparticles. [58][59][60][61][62][63][64][65][66][67] Since the discovery of DLCs, there has been tremendous interest in utilizing these materials as one-dimensional semiconductors. Conducting and photoconducting properties of DLCs have been studied extensively.…”
Section: Liquid Crystals In Photovoltaics M Kumar and S Kumarmentioning
confidence: 99%
“…The PR grating with a period of about 410 nm was fabricated on glass substrate with a 200-nm layer of indium tin oxide (ITO), where the ITO layer also acts as a waveguide. Chemically synthesized gold nanoparticles [15,16] with a diameter ranging from 5 to 10 nm, which were suspended in xylene with a concentration of 100 mg/mL, were then spin-coated onto the top surface of the grating. In the spin-coating process, a 30-μL colloidal solution of gold was spin-coated at a speed of 2000 rpm.…”
Section: Fabrication and Characterization Of The Plasmonic Gold Nanowmentioning
confidence: 99%